Comparing the effects of marking techniques on the survival of Piping Plover chicks - Christy N. Wails; Daniel H. Catlin; Samantha G. Robinson; Henrietta A. Bellman; Katie W. Oliver; Hope L. VanDerwater; Sharon S. Dorsey; Audrey DeRose-Wilson; Sarah M. Karpanty; James D. Fraser (Journal of Ornithology, 2025)
The use of unique markers in ornithology has a long history and is predicated on the assumption that markers have negligible effects on behavior and survival. The assumption that marks are harmless is particularly important with imperiled species. We studied the effects of two different marking schemes on Piping Plovers ( Charadrius melodus ), a small shorebird protected under the U.S. Endangered Species Act that is intensively monitored and managed. We used two marking schemes, (1) color bands and (2) uniquely engraved flags during breeding seasons from 2013 to 2023 to determine whether the injuries were causing additive mortality and thus actually limiting populations. We estimated the effect of perceived limping and injury (e.g., swelling, laceration, etc.) on chick and hatch-year survival. We detected injuries in some years and associated with both marking schemes (range 0.0–6.0%, average = 2.7% of marked chicks each year). Interval survival for banded chicks was like that of flagged chicks ( $$β $$ β = − 0.55, 95% BCI: − 1.30–0.33, f = 0.92). Mean survival to fledging, however, was higher in years where flags were used ( $$\overline{φ }=$$ ϕ ¯ = 0.55 ± 0.14) than when bands were used ( $$\overline{φ }=$$ ϕ ¯ = 0.34 ± 0.14), but we surmise that this difference was partly conflated with negative density-dependent factors ( $$β $$ β = − 0.49, 95% BCI: − 0.73 to − 0.25, f = 1.00) and predation. Our results show that pre-fledge survival of birds with uniquely coded flags was similar to that of birds receiving color bands. There was also no evidence that injured birds had a significantly lower hatch-year survival than those that were not injured. However, the relatively high (up to 6%) injury rate in some years remains a concern. Injury and survival rates need to be considered and evaluated when deciding on whether to mark individuals. Ultimately, wildlife practitioners should strive to use the best methods for information gathering and management, without negatively impacting the species.